The Role of Psychological Empowerment in Mediating the Influence of Transformational Leadership, Innovative Work Behavior and Career Development on Employee Retention - Prayogo, Rizki; Indrayanto, Adi; Daryono, Daryono (Jurnal Akuntansi, Manajemen dan Ekonomi, 2025)
This study aims to determine the role of psychological empowerment as a mediator between transformational leadership, innovative work behavior, and career development in influencing employee retention at Universitas Muhammadiyah Purwokerto. This quantitative research uses cross-sectional data collection techniques with 100 respondents. The results of the SEM-PLS analysis show that: (1) Transformational Leadership does not have a significant effect on Employee Retention, (2) Innovative Work Behavior has a positive effect on Employee Retention, (3) Career Development does not have a significant effect on Employee Retention, (4) Psychological Empowerment has a positive effect on Employee Retention, (5) Psychological Empowerment partially mediates the effect of Transformational Leadership and Career Development on Employee Retention, and fully mediates the effect of Innovative Work Behavior on Employee Retention. The implication of these findings is that Universitas Muhammadiyah Purwokerto can design more effective retention strategies by considering inspirational leadership, innovation, career development, and psychological empowerment to create a motivating work environment, thereby improving overall employee retention.